Collaboration Comics in Teaching Practitioner Program - Rizki Taufik Rakhman; Rizky Wardhani; Iwan Gunawan (Future Science, 2023)
Practical teaching is a program initiated by the Ministry of Education, Culture, Research and Technology of the Republic of Indonesia so that college graduates are better prepared to enter the world of work. The Fine Arts Education study program responds to the practitioner teaching program in illustration courses. The research entitled,